2020
DOI: 10.1016/j.jid.2019.06.148
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Calpain Externalization by Reducing ABCA1 Activity with Probenecid Limits Melanoma Angiogenesis and Development

Abstract: Calpains, intracellular proteases specifically inhibited by calpastatin, play a major role in neoangiogenesis involved in tumor invasiveness and metastasis. They are partly exteriorized via the ATP-binding cassette transporter A1(ABCA1) transporter, but the importance of this process in tumor growth is still unknown. The aim of our study was to investigate the role of extracellular calpains in a model of melanoma by blocking their extracellular activity or exteriorization. In the first approach, a B16-F10 mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Past studies have shown that ABCA1 is a lipid transporter protein that plays an important role in maintaining HDL biosynthesis and cellular cholesterol homeostasis ( 64 ). Numerous studies have demonstrated that ABCA1 was associated with the development of a variety of cancers, including colon cancer ( 65 , 66 ), myeloproliferative neoplasms ( 67 ), ovarian cancer ( 68 , 69 ), prostate cancer ( 70 ), and melanoma ( 71 ). ABCA1 may have a dual role in cancer, with ABCA1 showing anti-cancer effects in breast and prostate cancers, but pro-cancer effects in colorectal, bladder and melanoma cancers ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown that ABCA1 is a lipid transporter protein that plays an important role in maintaining HDL biosynthesis and cellular cholesterol homeostasis ( 64 ). Numerous studies have demonstrated that ABCA1 was associated with the development of a variety of cancers, including colon cancer ( 65 , 66 ), myeloproliferative neoplasms ( 67 ), ovarian cancer ( 68 , 69 ), prostate cancer ( 70 ), and melanoma ( 71 ). ABCA1 may have a dual role in cancer, with ABCA1 showing anti-cancer effects in breast and prostate cancers, but pro-cancer effects in colorectal, bladder and melanoma cancers ( 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…Letavernier et al noted that externalization of calpains’ activity increased when endothelial cells were exposed to VEGF-A and norepinephrine ( 37 ). Secretory modalities include cellular vesicles ( 38 ) or, via the ATP-binding cassette transporter A1 (ABCA1) ( 39 ). In the other way of externalization, calpains released from dying cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calpain externalization from human umbilical ECs is reportedly potentiated by physiological stressors, such as VEGF and norepinephrine [39]. More recent, Hanouna et al noted that calpain externalization is prevented by siRNA-based silencing of ABCA1; thus, those processes are probably driven through the molecular machinery [41]. Another possible mechanism underlying calpain externalization is a leakage from deadly cells.…”
Section: Calpains Play Pivotal Roles In the Inflammatory Properties Omentioning
confidence: 99%